Post-natal development of rats` offspring treated with the ethanol extract of Neem leaves (Azadirachta indica A. Juss) during pregnancy and lactation - Silva, Vanessa Carla Lima da; Silva, Francine Maria de França; Meunier, Isabelle Maria Jacqueline; Silva, Tânia Maria Sarmento da; Silva Júnior, Valdemiro Amaro da; Maia, Frederico Celso Lyra (Acta Scientiarum. Biological Sciences, 2015)
Teratogenicity and developmental abnormalities in the offspring of female rats that ingested ethanol extract of Neem plants during pregnancy and lactation period were assessed. Twenty-four female Wistar rats were randomly distributed in control group and in three experimental groups and treated during the 4th, 5th, and 6th day of pregnancy. After birth, the lactating females received, by gavage, 65, 135 and 200 mg kg-1 of Neem ethanol extract, during 15 days. Results show, there was no significant difference in body mass index of neonatal rats in the 4 groups evaluated, whereas mean rate of offspring survival was 79.4%. Hair growth, incisor teeth eruption, ear detachment, eyelid opening, and spontaneous ambulation were similar for all groups. Likewise, physical development and development of motor activity, ambulation, and postural reflexes were similar for all groups. The administration of Neem ethanol extract did not cause any reproductive or systemic toxicity in animals. Results show that, Neem ethanol extract safe at doses 65, 135 and 200 mg kg-1 in pregnant or lactating rats.